Mentalizing impairments in somatic symptom disorder: a systematic review and meta-analysis - Kocsis-Bogar, Krisztina; Deri, Judit; Miklósi, Mónika; Wildner, Brigitte; Kaltenboeck, Alexander; Aichberger, Marion C. (Frontiers in Psychology, 2026)
BackgroundMentalizing deficits have been observed across various psychiatric disorders, but there is currently no systematic review or meta-analysis about the differences of mentalizing performance in patients with somatic symptom disorder (SSD) compared to non-clinical or clinical controls. The aim of the present paper is to fill this gap.MethodA systematic search of databases, including Embase, MEDLINE, CENTRAL, PsycInfo, Psyndex, LILACS, Scopus, Web of Science, OpenGrey and Open Doar was conducted up to June 2025.ResultsAltogether 3,796 records were identified and screened according to the PRISMA guidelines. Ten cross-sectional case-controls studies in patients with SSD and controls (12 publications, N = 314) were found eligible for our review, out of which nine studies were included in our meta-analysis. High risk of bias and modest methodological quality was found in the majority of the studies using the AHRQ method. SSD patients demonstrated significant impairments in mentalizing in general as well as in mentalizing about cognitive and affective states (p = 0.001) compared to non-clinical controls. A homogeneous effect of undermentalizing (p = 0.007) was observed compared to non-clinical controls, though no significant mentalizing differences were found between the observed patient group and patients with major depressive disorder (MDD) or posttraumatic stress disorder (PTSD).ConclusionPatients with SSD exhibit reduced mentalizing performance compared to non-clinical controls, but no mentalizing deficit could be shown compared to those with MDD or PTSD, likely due to the limited number and methodological heterogeneity of relevant studies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=462714